Biodiversity of Dickeya spp. Isolated from Potato Plants and Water Sources in Temperate Climate - Potrykus, Marta (Plant disease, 2016)
Bacteria from the genera Dickeya (formerly Erwinia chrysanthemi) and Pectobacterium (formerly E. carotovora) are the agents of blackleg and soft rot on many important crops. In 2005, Dickeya solani was isolated for the first time in Poland from a symptomatic potato plant. To establish the presence and diversity of Dickeya spp. in Poland, we surveyed potato fields and water sources, including surface waters near potato fields and water from potato-processing facilities and sewage plants. Only D. dianthicola and D. solani were isolated from symptomatic potato, and only D. zeae and D. chrysanthemi were isolated from water sources. The Dickeya spp. isolated from potato formed a relatively homogenous group, while those from water sources were more diverse. To our knowledge, this is the first comprehensive characterization of Dickeya spp. isolated during several years from regions with a temperate climate in Central Europe